STUDI TRANSPOR SEDIMEN LITHOGENEUS DI PERAIRAN MUARA SUNGAI DUMAI PROVINSI RIAU - Asrori '; Rifardi '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study was conducted in January 2016 in the estuary of Dumai River, Province of Riau Indonesia, aims to determine the amount of the lithogeneus sediment, which flow through the Dumai River, and were deposited in the Estuary Dumai River. The estuary were divided into eight (8) sampling point. The result of this study showed that the Estuary of Dumai River is influenced by the water mass flow through the River (13.81 m3/s) which supply the lithogeneus sediment as much 4,644.03 gr/s or 165.6 tons/year and are deposited 0,0175 gr/cm2/day or 6,3 gr/cm2/year.Keywords: Sediment Transport, Lithogeneus Sediment, Dumai River